2008
DOI: 10.1007/s12031-008-9162-7
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Antagonized 1-Methyl-4-Phenylpyridinium (MPP+)-Induced Apoptosis in MES23.5 Cells

Abstract: Ghrelin is an endogenous ligand for the growth hormone secretagogue receptor (GHS-R) acting to stimulate growth hormone release. In the previous study, we have observed the neuroprotective effects of ghrelin on dopaminergic neurons in vivo in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine -treated Parkinson's disease mice. In order to illustrate the underlying mechanisms, in the present study, we conducted our experiment in vitro in 1-methyl-4-phenylpyridinium (MPP(+))-treated MES23.5 cells that could express GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Cell viability was expressed as a percentage of the absorbance from control cells. The toxic effects of 6-OHDA to SH-SY5Y cells were also detected by measuring the leakage of the cytosolic enzyme LDH to the culture medium using a colorimetric LDH assay kit (KeyGen, China) according to the manufacturer’s instructions [17]. Briefly, after 100 μM 6-OHDA added, 20 μl of cell medium were added into basic solution to measure extracellular LDH activity, which could catalyze the conversion of lactate to pyruvate, which then reacted with 2,4-dinitrophenylhydrazine to give the brownish red color.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was expressed as a percentage of the absorbance from control cells. The toxic effects of 6-OHDA to SH-SY5Y cells were also detected by measuring the leakage of the cytosolic enzyme LDH to the culture medium using a colorimetric LDH assay kit (KeyGen, China) according to the manufacturer’s instructions [17]. Briefly, after 100 μM 6-OHDA added, 20 μl of cell medium were added into basic solution to measure extracellular LDH activity, which could catalyze the conversion of lactate to pyruvate, which then reacted with 2,4-dinitrophenylhydrazine to give the brownish red color.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated that apoptosis induced by mitochondrial dysfunction plays important roles in the development of PD678, indicating that the prevention of apoptosis could be a therapeutic strategy for PD. In our previous studies, we reported that ghrelin, which is secreted by X/A-like cells in the gastric glands, showed neuroprotective effects on dopaminergic neurons exposed to the toxin 1-methyl-4-phenyl-1, 2,3,6-tetrahydropyridine (MPTP) both in vivo and in vitro via an anti-apoptotic effect mediated by the ghrelin-protein kinase C (PKC) signaling pathway91011.…”
mentioning
confidence: 99%
“…Recent studies have reported that ghrelin could inhibit apoptosis in several cell lines via GHS-R1a [16][17][18] . Our previous study has also revealed the neuroprotective effects of ghrelin on dopaminergic neurons [7,8] . Zeenat Atcha et al have reported that ghrelin receptor agonists can elicit pro-cognitive effects in recognition and spatial learning and memory tests [19] .…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, in the present study, adenovirus vectors were employed to transfer the target gene. Previous studies have demonstrated that ghrelin, a newly identified 28-amino acid brain-gut peptide, can inhibit apoptosis in Parkinson's disease (PD) models both in vitro and in vivo, through its receptor: growth hormone secretagogue receptor type 1a (GHS-R1a) [7,8] . Besides, it has been reported that ghrelin receptor agonists elicit pro-cognitive effects and can enhance spatial learning and memory.…”
Section: Introductionmentioning
confidence: 99%